2005
DOI: 10.1161/01.res.0000170888.11669.28
|View full text |Cite
|
Sign up to set email alerts
|

COX-2–Derived Prostacyclin Modulates Vascular Remodeling

Abstract: Abstract-Suppression of prostacyclin (PGI 2 ) biosynthesis may explain the increased incidence of myocardial infarction and stroke which has been observed in placebo controlled trials of cyclooxygenase (COX)-2 inhibitors. Herein, we examine if COX-2-derived PGI 2 might condition the response of the vasculature to sustained physiologic stress in experimental models that retain endothelial integrity. Deletion of the PGI 2 receptor (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
2
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(88 citation statements)
references
References 54 publications
4
78
2
3
Order By: Relevance
“…The observed reduction in blood flow in IP À/À mice may, however, have an additional explanation. It was recently shown that IP À/À mice display an increased proliferative response and decreased luminal area weeks after vascular injury (Cheng et al, 2002;Rudic et al, 2005), and we cannot exclude that the decreased blood flow 24 h after trauma may, in part, be explained by such an effect.…”
Section: Discussionmentioning
confidence: 87%
“…The observed reduction in blood flow in IP À/À mice may, however, have an additional explanation. It was recently shown that IP À/À mice display an increased proliferative response and decreased luminal area weeks after vascular injury (Cheng et al, 2002;Rudic et al, 2005), and we cannot exclude that the decreased blood flow 24 h after trauma may, in part, be explained by such an effect.…”
Section: Discussionmentioning
confidence: 87%
“…The basic literature is replete with recent studies demonstrating that genomic or pharmacological removal of prostacyclin leads to both platelet-dependent [13][14][15] and plateletindependent 16 mechanisms for induction of thrombosis, plaque destabilization, or atherogenesis. In addition, COX-2 is recognized as a key source of prostacyclin under normal laminar flow conditions in the vasculature and has been shown to be cardioprotective in ischemia-reperfusion injury.…”
Section: Pharmacology Of Cox Inhibitionmentioning
confidence: 99%
“…Mechanistically, this is attributable to suppression of COX-2-derived prostacyclin (PGI 2 ; ref. 6), which acts as a general restraint on endogenous stimuli, including platelet COX-1-derived thromboxane (Tx) A 2 , to platelet activation, vascular proliferation and remodeling, hypertension, atherogenesis, and cardiac function (7)(8)(9)(10)(11)(12)(13). Precise estimates of the incidence of this risk are not available.…”
mentioning
confidence: 99%